Determinants of Utilization of Institutional Delivery Services in East Nepal: A Community-Based Cross- Sectional Study (Med Phoenix, 2018)
Background: In this study, we expected to evaluate the utilization rate of institutional delivery services in Eastern Nepal. We also analyzed the socio-economic factors associated with institutional delivery and assessed the reason for their utilization.Methods: A cross-sectional quantitative study was conducted in Sunsari district of Eastern Nepal. Three hundred and seventy two women, who delivered their baby within period of one year preceding this study, were interviewed through household visit. Focus group discussions (FGDs) were also done to gather qualitative data.Results: We interviewed 368 women. The prevalence of institutional delivery was 55.1%. Logistic regression analyses revealed that women having good knowledge about importance of SBA utilized institutional delivery services more than nine times than women having poor knowledge (AOR=9.02, 95% CI: 2.61-31.09). Similarly, women exposed to media (AOR=6.56, 95% CI: 2.10-21.21), women from advantaged ethnicity (AOR=5.85, 95% CI: 1.78-19.74), women having higher level of autonomy (AOR= 5.93, 95%CI: 1.18- 29.53) and richer women (AOR=3.30, 95% CI: 1.24-8.72) were more likely to have institutional delivery than women unexposed to media, women from relatively disadvantaged ethnicity, women having low level of autonomy and poorer women respectively.Conclusions: Good knowledge on importance of SBA, completion of 4 ANC service, media exposure with maternal health service related massages, relatively advantaged ethnicity, higher rank of women’s autonomy and higher wealth rank were found significantly associated with institutional delivery service utilization. Provisions of community ambulance system can also be helpful to address the transportation problem. Encouraging women to complete their schooling and teaching/encouraging women to have antenatal care frequently are also important to increase institutional delivery services. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 6-15